Analysis of the Physical Quality of the University of Riau's Science Park Public Open Space - Oriana Paramita Dewi; Laili Dwi Annisa; Nurrul Helen (PT FORMOSA CENDEKIA GLOBAL, 2023)
The growth of the city of Pekanbaru as one of the big cities in Indonesia can be said to be quite rapid, but the growth of this city has not been matched by the growth of green open spaces. The University of Riau also contributes to developing a green campus environment, one of which is the construction of the Science Park Public Open Space. But unfortunately this RTP is still less attractive to the local community. This study aims to determine the physical quality of RTP Science Park with the scoring method. The initial stage was a literature study, followed by field observations in the form of identification of the physical quality of the RTP, which was then given an assessment of each aspect. The results of the study show that the access variable has a very good value while the other variables have a bad value so that it requires changes/addition which will later be given recommendations to improve the quality of the RTP.